Dissecting the Metabolic Role of Mitochondria during Developmental Leaf Senescence - Chrobok, Daria (Plant Physiol, 2016)
The functions of mitochondria during leaf senescence, a type of programmed cell death aimed at the massive retrieval of nutrients from the senescing organ to the rest of the plant, remain elusive. Here, combining experimental and analytical approaches, we showed that mitochondrial integrity in Arabidopsis (Arabidopsis thaliana) is conserved until the latest stages of leaf senescence, while their number drops by 30%. Adenylate phosphorylation state assays and mitochondrial respiratory measurements indicated that the leaf energy status also is maintained during this time period. Furthermore, after establishing a curated list of genes coding for products targeted to mitochondria, we analyzed in isolation their transcript profiles, focusing on several key mitochondrial functions, such as the tricarboxylic acid cycle, mitochondrial electron transfer chain, iron-sulfur cluster biosynthesis, transporters, as well as catabolic pathways. In tandem with a metabolomic approach, our data indicated that mitochondrial metabolism was reorganized to support the selective catabolism of both amino acids and fatty acids. Such adjustments would ensure the replenishment of α-ketoglutarate and glutamate, which provide the carbon backbones for nitrogen remobilization. Glutamate, being the substrate of the strongly up-regulated cytosolic glutamine synthase, is likely to become a metabolically limiting factor in the latest stages of developmental leaf senescence. Finally, an evolutionary age analysis revealed that, while branched-chain amino acid and proline catabolism are very old mitochondrial functions particularly enriched at the latest stages of leaf senescence, auxin metabolism appears to be rather newly acquired. In summation, our work shows that, during developmental leaf senescence, mitochondria orchestrate catabolic processes by becoming increasingly central energy and metabolic hubs.